2004
DOI: 10.3748/wjg.v10.i19.2791
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative adjuvant arterial chemoembolization improves survival of hepatocellular carcinoma patients with risk factors for residual tumor: A retrospective control study

Abstract: AIM:To evaluate the effect of postoperative adjuvant transcatheter arterial chemoembolization (TACE) on the prognosis of hepatocellular carcinoma (HCC) patients with or without risk factors for the residual tumor. METHODS:From January 1995 to December 1998, 549 consecutive HCC patients undergoing surgical resection were included in this research. There were 185 patients who underwent surgical resection with adjuvant TACE and 364 patients who underwent surgical resection only. Tumors with a diameter more than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 25 publications
3
66
0
Order By: Relevance
“…2,26 Other factors such as tumour size > 10 cm and poor tumour differentiation were also related to increased recurrence in the present series, but their effects were not noticeable on multivariate analysis. Presence of satellite tumour nodules around the main tumour has been reported in many series; [5][6][7][8] this may well be an indicator of the invasiveness of the primary tumour, and it had a negative effect on disease-free survival in the present series. Venous invasion via the portal system was believed to be responsible for intrahepatic metastasis and consequently intrahepatic recurrence.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…2,26 Other factors such as tumour size > 10 cm and poor tumour differentiation were also related to increased recurrence in the present series, but their effects were not noticeable on multivariate analysis. Presence of satellite tumour nodules around the main tumour has been reported in many series; [5][6][7][8] this may well be an indicator of the invasiveness of the primary tumour, and it had a negative effect on disease-free survival in the present series. Venous invasion via the portal system was believed to be responsible for intrahepatic metastasis and consequently intrahepatic recurrence.…”
Section: Discussionsupporting
confidence: 61%
“…7 In contrast, Ren et al demonstrated that postoperative adjuvant TACE can prolong the survival of patients with risk factors for residual tumour, but could not prolong the survival of patients without risk factors for residual tumour. 8 In a recent meta-analysis the authors suggested that the use of postoperative transarterial chemotherapy with or without embolization may improve survival. 9 At the present time there is no consensus regarding the use of TACE in an adjuvant settings; patient treatment should be based on individual consideration of personal risks and benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that adjuvant TACE can prolong survival of patients with risk factors for residual tumor (41). Here, we show that adjuvant TACE can reduce early recurrence after surgery in CD24 + patients only.…”
Section: Discussionmentioning
confidence: 99%
“…As for the treatment for LNM, our study suggested that for patients who are CK19(1), in view of the high incidence of LNM resulting from its ICC-like differentiation and its tendency to metastasize to a further LNM location, we suggest that routine regional lymphadenectomy could be performed to obtain a precise stage and its consequential prognostic significance; moreover, chemotherapy with gemcitabine and docetaxel could be tried because of their ICC-like characteristics, 26 whereas in CK19(2) patients regional lymphadenectomy might not be suitable because of the lower incidence of LNM as in pure HCC. Instead, conventional adjuvant chemoembolization 27 or interferon-a 28 as well as external beam radiotherapy 29 might be effective for improving prognosis. Overall, further exploration of the pertinent treatment modalities for different CK19 expression groups of HCC with LNM should be pursued in larger cohorts of patients.…”
Section: Discussionmentioning
confidence: 99%